2017
DOI: 10.17219/acem/65783
|View full text |Cite
|
Sign up to set email alerts
|

Do medical students adhere to advice regarding a healthy lifestyle? A pilot study of BMI and some aspects of lifestyle in medical students in Poland

Abstract: Background. The components of lifestyle of medical students, with comprehensive reporting of their physical activity and drinking and eating behavior, are rarely evaluated. Being overweight (increased body mass index -BMI) is associated with health problems, an unhealthy lifestyle (inadequate sleep, diet and exercise) being implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
4
10
0
3
Order By: Relevance
“…Inline to our findings, Deng et al also reported the high prevalence of overweight and obesity in students with high educational levels [ 43 ]. We found a negative association of sleeping duration with BMI, these results was consistent with an earlier study [ 44 ]. In our study, there was negative association of BMI with physical exercise.…”
Section: Discussionsupporting
confidence: 93%
“…Inline to our findings, Deng et al also reported the high prevalence of overweight and obesity in students with high educational levels [ 43 ]. We found a negative association of sleeping duration with BMI, these results was consistent with an earlier study [ 44 ]. In our study, there was negative association of BMI with physical exercise.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, breakfast skipping is congruent with the findings of Sun et al ( 23 ) who reported a prevalence of 41.7%. No association was found between breakfast skipping and body mass index, in accordance with a study conducted in Poland ( 24 ), and concluded similar results. The current data showed an association between fruit and vegetable consumption and body mass index, whereas a previous study ( 25 ) found no association between fresh fruits and vegetables and obesity, supporting the current observation.…”
Section: Discussionsupporting
confidence: 90%
“…In another cross-sectional survey in the UAE, a large percentage of medical students were found to be either underweight or obese and most were found to believe that their activity levels were insufficient, stress levels too high, and diets unhealthy [15]. A pilot study on medical students in Poland showed non-adherence to advise regarding a healthy lifestyle with regard to sleep, food and fluid intake, and exercise [16]. A local study on the medical students of the Aga Khan University, Pakistan, showed that the majority (>90%) of students thought they had been stressed at one time or another, which affected not only their academic performances but also all aspects of health [17].…”
Section: Discussionmentioning
confidence: 99%